Wound healing and antibacterial activities of water-soluble chitosan nanoparticles and excretion/secretion as a natural combination from medicinal maggots, Lucilia cuprina. (November 2021) - Abdel-Samad, Mohammad RK; Taher, Fatma A
Wounds management takes a high interest in the medical field and the addition of antimicrobial agents in an assortment of wound dressings leads to delay the wound healing. This study aimed at preparing natural combination between excretion/secretion (ES) and water-soluble chitosan nanoparticles (from Lucilia cuprina maggots) and investigating its antibacterial and wound healing activities. ES of maggots was collected, and the water-soluble chitosan nanoparticles (WSCNPs) were prepared and characterized. Antibacterial activities of combinations were evaluated against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Proteus vulgaris . ES-WSC-2 combination that contains 50% ES and 1% WSCNPs showed highest antibacterial activity against all tested bacteria compared to the other combinations. In vitro, the ES-WSC-2 combination was used to study the wound healing activity by scratch assay. The synergism between ES and WSCNPs (in ES-WSC-2 combination) accelerated the wound healing rate which suggests the use of this combination as an effective natural antibacterial and wound healing agent.